Organoids-on-a-chip: microfluidic technology enables culture of organoids with enhanced tissue function and potential for disease modeling - Papamichail, Lito; Koch, Lena S.; Veerman, Devin; Broersen, Kerensa; van der Meer, Andries D. (Frontiers in Bioengineering and Biotechnology, 2025)
Organoids are stem-cell derived tissue structures mimicking specific structural and functional characteristics of human organs. Despite significant advancements in the field over the last decade, challenges like limited long-term functional culture and lack of maturation are hampering the implementation of organoids in biomedical research. Culture of organoids in microfluidic chips is being used to tackle these challenges through dynamic and precise control over the organoid microenvironment. This review highlights the significant breakthroughs that have been made in the innovative field of “organoids-on-chip,” demonstrating how these have contributed to advancing organoid models. We focus on the incorporation of organoids representative for various tissues into chips and discuss the latest findings in multi-organoids-on-chip approaches. Additionally, we examine current limitations and challenges of the field towards the development of reproducible organoids-on-chip systems. Finally, we discuss the potential of organoids-on-chip technology for both in vitro and in vivo applications.